2022
DOI: 10.1371/journal.pone.0266809
|View full text |Cite
|
Sign up to set email alerts
|

The associations between COVID-19 diagnosis, type 1 diabetes, and the risk of diabetic ketoacidosis: A nationwide cohort from the US using the Cerner Real-World Data

Abstract: Objective To assess the risk of new-onset type 1 diabetes mellitus (T1D) diagnosis following COVID-19 diagnosis and the impact of COVID-19 diagnosis on the risk of diabetic ketoacidosis (DKA) in patients with prior T1D diagnosis. Research design and methods Retrospective data consisting of 27,292,879 patients from the Cerner Real-World Data were used. Odds ratios, overall and stratified by demographic predictors, were calculated to assess associations between COVID-19 and T1D. Odds ratios from multivariable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 48 publications
0
65
0
Order By: Relevance
“…Whether COVID-19 could trigger auto-immunity in predisposed people remains unknown [ 57 ]. For example, a recent study showed an association between COVID-19 infection and development of type 1 diabetes, with a higher risk in younger (age 0–1) and older (51–65) people [ 89 ]. Whether this risk is higher in people with pro-inflammatory PI remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Whether COVID-19 could trigger auto-immunity in predisposed people remains unknown [ 57 ]. For example, a recent study showed an association between COVID-19 infection and development of type 1 diabetes, with a higher risk in younger (age 0–1) and older (51–65) people [ 89 ]. Whether this risk is higher in people with pro-inflammatory PI remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…We included Xie's cohort because it had a larger sample size, longer follow-up duration, and more adequate data. Additionally, 10 articles, including 11 cohorts, proved eligible [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , of which two articles were pre-printed [28] , [32] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of all the included cohorts. Seven of the 11 retrospective cohorts included populations from the United States [27] , [29] , [30] , [31] , [33] , [34] , three from Europe (England, Scotland, and Germany) [32] , [35] , [36] , and one from the global population [28] . Among all cohorts, >4.5 million participants with COVID-19 during the pandemic (after December 2019) and >42 million people without either COVID-19 or diabetes were included.…”
Section: Resultsmentioning
confidence: 99%
“…Kamrath et al 8 cautiously suggests that the incidence of T1D followed the peak incidence of COVID‐19 by approximately 3 months, we however do not think this could be interpreted as causation; moreover, neither Kamrath et al 8 nor we have individual COVID‐19 data. Studies using electronic medical records and medical claims might bring more insight ‐ of the published works, some 10 , 12 but not all 11 observed a link between COVID‐19 and an increase in pediatric diabetes incidence.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 Recently, studies have been published that utilized big collections of electronic health records or medical claims, reporting conflicting results. 10 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%